2002
DOI: 10.1097/00001888-200206000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Professional Behavior

Abstract: A circumscribed concept of professionalism is available to serve as a foundation for next steps in assessing professional behavior. The current array of assessment tools is rich. However, their measurement properties should be strengthened. Accordingly, future research should explore rigorous qualitative techniques; refine quantitative assessments of competence, for example, through OSCEs; and evaluate separate elements of professionalism. It should test the hypothesis that assessment tools will be better if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
73
0
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 401 publications
(78 citation statements)
references
References 92 publications
2
73
0
3
Order By: Relevance
“…Various authors have proposed that women show higher levels of empathy compared to men [7]- [9] and those empathy measurements, of those investigations, have been performed with different instruments developed for the general population and the medical field. On the other hand, some authors have proposed, with theoretical basis and less empirical evidence, that empathy could be a "variable" that is subjected to the influence of several factors, in addition to the gender [10]- [12], as well as age, intent about the specialty to follow in the future, the current course the student is taking, structure and family environment, personality, empathetic experiences, socio-cultural environment, scale of ethical and moral values, among others; which could act as independent "variables" or confounding variables, and at the same time, could contribute to explain the variability observed in empathetic orientation levels found in some research [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Various authors have proposed that women show higher levels of empathy compared to men [7]- [9] and those empathy measurements, of those investigations, have been performed with different instruments developed for the general population and the medical field. On the other hand, some authors have proposed, with theoretical basis and less empirical evidence, that empathy could be a "variable" that is subjected to the influence of several factors, in addition to the gender [10]- [12], as well as age, intent about the specialty to follow in the future, the current course the student is taking, structure and family environment, personality, empathetic experiences, socio-cultural environment, scale of ethical and moral values, among others; which could act as independent "variables" or confounding variables, and at the same time, could contribute to explain the variability observed in empathetic orientation levels found in some research [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
“…Several reviews on the assessment of professionalism have shown that the measurement of professionalism is problematic [8][13]. The reviews identified many different methods for assessing professionalism, a lack of consensus on the definition of professionalism, changing views of professionalism over time and the limited reporting of validity and reliability issues [10], [12].…”
Section: Introductionmentioning
confidence: 99%
“…This blending of elements related to professional behaviours has been noted in previous reviews in which communication skills, ethics, interpersonal skills, or patient relations were seen as a part of the professional behaviour elements being assessed rather than as distinct categories. 1,[19][20][21][22] In the Essential Competency Profile for Physiotherapists in Canada, 2 the interwoven nature of these behaviours is seen in the role descriptions of both communicator and professional. The role of communicator is presented as the vehicle for achieving professional relationships; the role of professional has respect as one of its three key competencies.…”
Section: Discussionmentioning
confidence: 99%
“…1 In the Essential Competency Profile for Physiotherapists in Canada, professional is defined as ''committed to the best interests of clients and society through ethical practice, support of profession-led regulation, and high personal standards of behaviour.'' 2(p. 14) This broad and complex construct presents challenges to educators responsible for teaching and assessing competencies related to professional behaviour.…”
mentioning
confidence: 99%